2020
DOI: 10.3390/insects11040261
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mortality and Adaptation of a Smurf Assay in Two Species of Tenebrionid Beetles Exposed to Bacillus thuringiensis

Abstract: Bacillus thuringiensis is a spore-forming bacterium which infects insect larvae naturally via the oral route. Its virulence factors interact with the epithelium of the digestive tract of insect larvae, disrupting its function and eventually leading to the death of susceptible hosts. The most cited B. thuringiensis killing mechanism is the extensive damage caused to the insect midgut, leading to its leakage. The mortality caused by B. thuringiensis has been shown to vary between serovars and isolates, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(70 reference statements)
0
2
1
Order By: Relevance
“…Bt tolworthi carries a different Cry toxin than Btt , namely, Cry3Ba. Even though this toxin has a high affinity to receptors of the midgut epithelial cells of T. castaneum ( Contreras et al, 2013 ) and another Bt strain carrying Cry3Ba caused mortality and priming ( Futo et al, 2017 ), Bt tolworthi did not induce significant mortality or priming in the present and previous studies ( Milutinović et al, 2013 ; Zanchi et al, 2020 ). LEfSe analysis showed that one taxon belonging to Bacillus is more abundant also in the Bt407 – priming treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…Bt tolworthi carries a different Cry toxin than Btt , namely, Cry3Ba. Even though this toxin has a high affinity to receptors of the midgut epithelial cells of T. castaneum ( Contreras et al, 2013 ) and another Bt strain carrying Cry3Ba caused mortality and priming ( Futo et al, 2017 ), Bt tolworthi did not induce significant mortality or priming in the present and previous studies ( Milutinović et al, 2013 ; Zanchi et al, 2020 ). LEfSe analysis showed that one taxon belonging to Bacillus is more abundant also in the Bt407 – priming treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…The genera Bacillus and Serratia are indeed well-known for their pathogenicity by both oral and septic injury routes among insects. S. marcescens is capable of crossing the gut epithelium in Drosophila melanogaster by traversing the enterocytes (32), and some Bacillus species are employed in oral infection protocols in insects (11,21,33,34), such as Bacillus thuringiensis, which produce crystalline proteins that disrupt the gut epithelium (35)(36)(37). In both cases, bacteria can reach the hemocoel, where they multiply and spread throughout the entire insect's body, leading to death by septicemia.…”
Section: Contaminated Food Did Not Kill Due To Efficient Behavioral A...mentioning
confidence: 99%
“…To our knowledge, only a few recent studies have explored infection or immune priming by the oral route in T. molitor. Zanchi et al (21) successfully infected T. molitor by feeding them with spores of Bacillus thuringiensis, while Dupriez et al (16) found that cultures of Serratia marcescens persist several days in the bran medium and increase mortality in T. molitor living in this contaminated food. These studies suggest that ecological conditions for oral pathogen infection and transmission exist for T. molitor.…”
Section: Introductionmentioning
confidence: 99%
“…The gut pH conditions and the presence of trypsin and chymotrypsin proteases determines the activation of the Bt protoxins in the 55 kDa toxin by proteolysis (Adang et al, 2014). The toxin is then able to bind to midgut receptors resulting in the leakage of the epithelium, allowing the spores or outgrown bacteria to access the haemocoel (Guo et al, 2021;Zanchi et al, 2020). The Bt strains along with several other strains from the Bacillus cereus group produce non-insect specific virulence factors like the metalloproteases InhA1 and InhA3 that might increase the success of infection by escaping the insect innate immune system through degradation of AMPs and deactivation of haemocytes (Dalhammar and Steiner, 1984) or enterotoxins that could play a role in pathogenesis (Kyei-Poku et al, 2007).…”
Section: Bacillus Thuringiensis Sv Morrisoni Biovar Tenebrionismentioning
confidence: 99%
“…Symptoms related to Bt infection are mainly correlated to reduced feeding behaviour, darker cuticle colour and larval death from septicaemia Zanchi et al, 2020)(Fig. 5).…”
Section: Bacillus Thuringiensis Sv Morrisoni Biovar Tenebrionismentioning
confidence: 99%